INFLUENCE OF SORPTION AND DESORPTION OF HYDROGEN AND OXYGEN ON THE PROCESSES OF MODIFYING AND CRYSTALLIZATION OF ALLOYS - V. Ju. Stetsenko (Литьë и металлургия)
It is shown that sorption and desorption of hydrogen and oxygen influence greatly on the processes of modifying.